Hubungan Pemeliharaan Anjing dengan Risiko Gigitan Hewan Penular Rabies di Sajingan dan Entikong (Wilayah perbatasan Indonesia-Malaysia) - Safaldy, Aizhar; Hernawan, Andri Dwi; Trisnawati, Elly; Arfan, Iskandar (Universitas Hang Tuah Pekanbaru, 2025)
Rabies remains a public health issue in the Indonesia–Malaysia border region. In early 2025, 16 suspected rabies-transmitting animal bite (GHPR) cases were reported in Sambas, while Sanggau also shows consistently high numbers. This cross-sectional study was conducted from January to March 2024, involving 348 purposively selected dog-owning households. Data were collected through questionnaires and observations and analyzed with Chi-Square and multivariate logistic regression. Keeping other animals, interaction with stray dogs, and irregular feeding were significantly linked to GHPR. The most influential factor was interaction with stray dogs (OR = 4.690). When all three factors occurred together, the predicted probability of GHPR reached 98.5%. Rabies prevention should focus on reducing contact between owned and stray dogs, supported by regular feeding, vaccination, and health monitoring.